Unsung heroes of old Japan - Isoda, Michifumi 1970- (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan))
"True stores of three little-known Japanese of the Edo period who lived lives of sublime selflessness and purity, blurring the boundary between self and others. Merchant Kokudaya J?uzabur?o comes up with a brilliant scheme to rescue his dying town from poverty. He and others go deep into debt, risking all to raise money for the cash-strapped daimyo and receive annual interest in return. Prodigious scholar and former Zen monk Nakane T?ori refuses a government post and elects to live in abject poverty, weaving sandals. Though perhaps the age's greatest poet, he throws his works into the fire and ends his days teaching in a country village. ?Otagaki Rengetsu, a noted beauty in Kyoto, loses two husbands and five children. She becomes a Buddhist nun and devotes her life to poetry and pottery. With her savings she feeds the hungry and builds a bridge across Kamo River"--Publisher's website.